How Do Medication Management Interventions Reduce Polypharmacy- Related Risks In Older Adults With Multiple Chronic Conditions? - Calista Giovani; Yudhi Hajianto Nugroho; Mutia Juliana (The International Journal of Medical Science and Health Research, 2025)
Introduction: Polypharmacy, defined as the concurrent use of five or more medications, is prevalent among older adults with multiple chronic conditions, increasing the risk of adverse drug events and diminished quality of life. Addressing these risks through effective medication management has become a critical healthcare priority. Methods: This systematic review evaluated 40 studies, primarily randomized controlled trials (RCTs), focusing on medication management interventions such as structured medication reviews, deprescribing protocols, and electronic decision support systems. The inclusion criteria targeted older adults aged 65 years and above, taking five or more medications. Results: The review revealed that medication management interventions significantly reduced the number of medications and potentially inappropriate medications (PIMs). Notably, 10 out of 14 studies reported a decrease in medication counts, and 5 out of 8 studies showed reductions in PIMs. Clinical benefits included improved quality-adjusted life years and fewer hospital admissions. Discussion: A multidisciplinary approach, involving pharmacists, physicians, and nurses, was essential for the success of these interventions. The integration of technology and patient-centered strategies enhanced medication adherence and safety. However, challenges such as time constraints and resource intensity hindered broader implementation. Conclusion: Medication management interventions effectively reduce polypharmacy-related risks in older adults. Continued focus on multidisciplinary collaboration, technology integration, and addressing implementation barriers is crucial for optimizing medication safety and health outcomes.